THE EFFECT OF SERVICE QUALITY AND PROMOTION ON CONSUMER REPURCHASE INTEREST IN BOLU MERANTI SHOP, MEDAN CITY - Putri Nabilla; Nur Hafni; Cut Sukmawati; Sufi; Maisyura (RADJA PUBLIKA, 2025)
This study aims to explore the influence of service quality and promotion on consumer repurchase intention of Bolu Meranti Shop in Medan City. This study is motivated by the high competition in the regional souvenir industry which requires every business actor to continue to maintain customer loyalty. The number of respondents in this study was 100 people, selected using a purposive sampling technique. The analytical method used was multiple linear regression analysis with the help of the SPSS version 30 program. The results of the study indicate that partially, the service quality variable has a positive and significant effect on consumer repurchase intention, so that the first hypothesis (H1) is accepted. Similarly, promotion also shows a positive and significant effect on repurchase intention, so that the second hypothesis (H2) is accepted. Simultaneously, both variables have a significant effect on consumer repurchase intention of Bolu Meranti Shop, so that the third hypothesis (H3) is accepted. These findings indicate that good service quality and appropriate promotional strategies can increase consumer repurchase intention. Therefore, Bolu Meranti Shop needs to continue to innovate in improving service quality and developing attractive promotional strategies to maintain consumer loyalty amidst competitive market competition.